The Concept of Sustainable Development and Its Impact on the Shaping of Modern International Relations through Global Agreements - Rydz-Żbikowska, Anna (Comparative Economic Research. Central and Eastern Europe, 2012)
The goal of this article is a depiction of the process of the molding of the concept of sustainable development as well as a look at the influence that this concept has exerted on contemporary international politics, especially taking into account agreements of worldwide scope. This article is also an effort at demonstrating that the foundations of the concept of sustainable development can be traced to certain economic theories. The final section of this article is devoted to the characteristics of individual conferences initiated by the United Nations in order to promote enduring and sustainable development on a world scale. Also presented are the achievements of the individual conferences and their roles in demarcating universally obligatory principles and standards of sustainable development.